Mobility and versatility of the liquid bismuth promoter in the working iron catalysts for light olefin synthesis from syngas. Issue 24 (5th June 2020) - Gu, Bang; Peron, Deizi V.; Barrios, Alan J.; Bahri, Mounib; Ersen, Ovidiu; Vorokhta, Mykhailo; Šmíd, Břetislav; Banerjee, Dipanjan; Virginie, Mirella; Marceau, Eric; Wojcieszak, Robert; Ordomsky, Vitaly V.; et al.
Abstract : Localization and migration of highly mobile and extremely efficient bismuth promoter in iron Fischer–Tropsch catalysts were elucidated using in situ methods. Abstract : Liquid metals are a new emerging and rapidly growing class of materials and can be considered as efficient promoters and active phases for heterogeneous catalysts for sustainable processes. Because of low cost, high selectivity and flexibility, iron-based catalysts are the catalysts of choice for light olefin synthesis via Fischer–Tropsch reaction. Promotion of iron catalysts supported by carbon nanotubes with bismuth, which is liquid under the reaction conditions, results in a several fold increase in the reaction rate and in a much higher light olefin selectivity. In order to elucidate the spectacular enhancement of the catalytic performance, we conducted extensive in-depth characterization of the bismuth-promoted iron catalysts under the reacting gas and reaction temperatures by a combination of cutting-edge in situ techniques: in situ scanning transmission electron microscopy, near-atmospheric pressure X-ray photoelectron spectroscopy and in situ X-ray adsorption near edge structure. In situ scanning transmission electron microscopy conducted under atmospheric pressure of carbon monoxide at the temperature of catalyst activation showed iron sintering proceeding via the particle migration and coalescence mechanism. Catalyst activation in carbon monoxide and in syngas leads to liquid bismuth metallic species, which readily migrate over the catalyst surface with the formation of larger spherical bismuth droplets and iron–bismuth core–shell structures. In the working catalysts, during Fischer–Tropsch synthesis, metallic bismuth located at the interface of iron species undergoes continuous oxidation and reduction cycles, which facilitate carbon monoxide dissociation and result in the substantial increase in the reaction rate.